A tunable physiomimetic stretch system evaluated with precision cut lung slices and recellularized human lung scaffolds - Rosmark, Oskar; Ibáñez-Fonseca, Arturo; Thorsson, Johan; Dellgren, Göran; Hallgren, Oskar; Larsson Callerfelt, Anna-Karin; Elowsson, Linda; Westergren-Thorsson, Gunilla (Frontiers in Bioengineering and Biotechnology, 2022)
Breathing exposes lung cells to continual mechanical stimuli, which is part of the microenvironmental signals directing cellular functions together with the extracellular matrix (ECM). Therefore, developing systems that incorporate both stimuli is urgent to fully understand cell behavior. This study aims to introduce a novel in vitro culture methodology combining a cyclic stretch that simulates in vivo breathing with 3D cell culture platforms in the form of decellularized lung scaffolds (DLS) and precision cut lung slices (PCLS). To this end, we have constructed a device that mimics the amplitudes and frequencies of distensions seen in the breathing human lung. For its validation, we cultured H441 lung epithelial cells in human DLS exposed to 16 stretch cycles per minute with a 10% stretch amplitude. Cell viability (resazurin reduction), proliferation (Ki-67) and YAP1 activation were evaluated at 24 and 96 hours by immunohistochemistry, while the expression of SFTPB, COL3A1, COL4A3 and LAMA5 was evaluated by qPCR. Cyclic stretch induced an increase in SFTPB expression after 24 hours without a concomitant increase in the stretch responsive gene YAP1. Moreover, the ECM milieu lowered the expression of the basement membrane protein genes COL4A3 and LAMA5 compared to tissue culture plastic control cultures, but no effect was observed by the mechanical stimuli. The device also confirmed good compatibility with PCLS culture, showing preserved morphology and metabolism in rat PCLS after 72 hours of mechanical stretch. Thus, we present a novel device and methodology for the easy assembling and study of lung tissue slice cultures subjected to physiomimetic mechanical stimuli, which shows promise for future studies of cell and tissue function in a lung ECM milieu with physiological or pathological mechanical stimuli.